Antihypertensive activity of ethanolic extract of Petroselinum sativum Hoffm "parsley" on L-NAME treated rats - Villarreal, Julian (2007)
The purpose of the present investigation was to determinate the antihypertensive activity of the ethanolic extract from Petroselinum sntivunJ "perejil"parsley in hypertensive rats. Four groups (n = 6), Holtzmann rats was used. The arterial hypertension in three groups was induced by administration of L-NAME 50 rng!kg/day orally for 11 days; of them, one group was administraled vehiele only, Ihe olhers groups were administrated parsley al dose 01 200 and 600 mglkglday, respectively; the fourth ene was the white and was administrated distilled water, !he treatment with parsley started two days after administration L-NAME and was daily. The arterial pressure was measured starting the experiment and aldays 2, 3, 4, 7 and 11. The SBP decreased significantly from firsl day 01 Irealmenl wilh parsley at dose of 600 rng!kgl day from 167,5 ± 1,5 mmHg up lo 148,5 + 2,9 mmHg (p < 0,001), the DBP decreased loo from 117,0 ± 3.7 mmHg up lo 97,3 + 3,9 rnmHg (p < 0,01). The SBP and DBP decreased loo 011 the second day 01 trealment at dose 01 200 mglkgldía. This effect was conlinued in both groups and at end 01 experiment, with 200 mg!kgldía Ihe SBP was 142,0 ± 1,37 mmHg, as long as with 600 rng!kg/día was 143,5 + 2,6 mmHg. In conc1usion, in experimental conditions of study, the ethanolic extract of Petroselinum sativum "perejil" parsley has antihypertensive effect in hypertensive rats for L-NAME.